Choosing the Right Color: A Way to Increase Sales - Nezhad, Zahra Hossein; Kavehnezhad, Katayoun (International Journal of Asian Social Science, 2013)
It can be stated that the colors are one of the most important and powerful tools of design for marketing materials such as web sites, direct mail, ads, and etc. Meanings and Usage of Color can vary from country to country. Therefore, it is necessary to identify each culture color psychology for correct use of color. This paper focuses on the psychological meaning of each color and suggests using it in the correct position. To this purpose the relationship between color and culture, gender, emotions and Costumer behavior are expressed. Findings of the study indicate that managers, Graphics’ designer and advertisers can use colors for increase Customer attention, and then use it to increase sales.